Key-controlled Rijndael algorithm with multiple S-boxes - YIN Xin-chun 1; YANG Jie 1; XIE Li 2 (Tongxin xuebao, 2007)
According to the design criterion of S-box in Rijndael algorithm,a number of S-boxes with good crypto-graphic properties were constructed,and the avalanche probabilities of these S-boxes were analyzed from variance point of view.Based on these studies,a key-controlled Rijndael algorithm with multiple S-boxes was proposed with the im-provement of SubBytes algorithm in Rijndael.Experimental results show that the improved algorithm has stronger ability to resist differential attack,and the avalanche effect of the algorithm is more reasonable.